Enhancing photostability and minimizing volatility of a promising drug candidate - Ruz Sanjuan, Vivian [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Rodríguez Chanfrau, Jorge Enrique [UNESP]; Calvo Alonso, Amalia María; Tabosa do Egito, Evyvaldo Sócrates; Van den Mooter, Guy; de Oliveira, Anselmo Gomes [UNESP] (Elsevier, 2024)
Microparticles (MP) composed of Ethylcellulose were developed to enhance the photostability and minimize the volatility of the antiprotozoal and antifungal compound 2-(2-nitrovinyl) furan (G-0). MP were prepared using the emulsion solvent evaporation method guided by a factorial design optimization approach. Characterization of the formulations was conducted through Thermal Analysis, FE-SEM microscopy, and X-ray diffraction. Additionally, drug-polymer interactions were analyzed using NMR and FTIR spectroscopy, while drug volatility was assessed by TGA/DTA. Forced photodegradation studies were conducted using a UV-light cabinet, and HPLC was employed for monitoring. The basket method was utilized for the drug release procedure. The resulting MP exhibited spherical morphology, reduced drug crystallinity, and good compatibility, as confirmed by ATR-FTIR and 1H NMR analysis. Microencapsulation led to improved photostability and reduced drug volatilization of G-0. The in vitro release of G-0 from MP was slower compared to the crystalline drug, and the release kinetics were well described by the First-order model. Further investigations will focus on accelerated stability studies on microencapsulated G-0 and compatibility assessments with other excipients to facilitate incorporation in solid formulations.
Keywords: 2-(2-nitrovinyl) furan; Drug release; Ethylcellulose; Microparticles; Photostabilization; Volatilization